VARIABEL ANTESEDEN DAN KONSEKUENSI PEMANFAATAN SISTEM INFORMASI (STUDI EMPIRIS PADA PEMERINTAHAN KABUPATEN DI PULAU MADURA) - Ellyana, Denovita Dwi; Redy, Achyar; Hamzah, Ardi (UI Scholars Hub, 2009)
The purpose of this research are (I) to give an empirical evidence that performance expectation, effort expectation, social factors, fit on tasks and conditions which facilitating user will affect the level o f interest in usage o f information system, and (2) to give an empirical evidence that interest in an usage o f information system will effect a utilization o f the information system. The respondents o f the research are employment that using information technology system in finishing its job. Data has gathered by questionnaires and documentation. Sample total is 50 respondents. The result o f research with partial regression indicated that variables o f antecedent are namely performance expectation, effort expectation, and conditions which facilitating a utilization o f the information system, significantly affect the interest o f usage the information system, while social factors andfit to task not significantly effect on interest in usage o f information system. The result o f research with partial regression indicated that variable o f consequence namely interest in usage o f information system significantly affect utilization information system.